2018
DOI: 10.23925/2176-2724.2018v30i3p-585-594
|View full text |Cite
|
Sign up to set email alerts
|

Potencial evocado auditivo de longa latência em crianças com desenvolvimento típico

Abstract: Introdução: O Potencial Evocado Auditivo de Longa Latência é utilizado para avaliar o processamento cortical da informação acústica. Objetivo: Descrever e comparar os valores de latência e amplitude do Potencial Evocado Auditivo de Longa Latência em crianças. Além disso, fornecer valores de referência. Material e Método: Estudo transversal e quantitativo, no qual foram avaliados 20 indivíduos com idade entre 5 e 9 anos e 11 meses, com desenvolvimento típico. Realizou-se tal potencial auditivo, com o equipament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…24 As for the P1 component, data from one study showed greater latency and amplitude for P1 in males. 29 The P1 component represents the entrance of the sound stimulus in the auditory cortex and, therefore, the anatomical difference that exists between the male and female skull can influence the propagation of the sound wave. Another hypothesis would be the non-homogeneity of the sample regarding gender.…”
Section: Discussionmentioning
confidence: 99%
“…24 As for the P1 component, data from one study showed greater latency and amplitude for P1 in males. 29 The P1 component represents the entrance of the sound stimulus in the auditory cortex and, therefore, the anatomical difference that exists between the male and female skull can influence the propagation of the sound wave. Another hypothesis would be the non-homogeneity of the sample regarding gender.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding LLAEP, the P3 component showed a significant increase in amplitude in the LE, a change that remained over time, as evidenced in the reassessment after 3 months of the intervention. It is known that amplitude is related to the magnitude of synaptic activity involved during perceptual processing of acoustic stimuli (12,29).…”
Section: ' Discussionmentioning
confidence: 99%